Changes in Lipids and Lipoprotein Indices in Relation to the Severity of Hypertension in Newly Diagnosed Hypertensive Nigerians. (19th November 2012) - Onwubuya, E. I.; Anisiuba, B. C.; Osuji, C. U.; Ahaneku, J. E.
Abstract : Hypertension and dyslipidaemia are important components of metabolic syndrome and both are known to complicate each other. Materials and Methods . A total of 149 subjects consisting of 107 hypertensive patients, grouped into 3 (of 37, 35, and 35 patients categorized based on the grade of hypertension as grade 1, grade 2, and grade 3, resp.) and 42 controls, were recruited for this study. Each subject had a recording of the bio- and anthropometric data comprising of the age, height, weight, body mass index (BMI), and abdominal circumference (AC). The blood pressure was also recorded. Fasting blood was collected and serum was used for the estimation of the lipids: total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglyceride (TG), while low density lipoprotein cholesterol (LDL-C) and VLDL were estimated using Friedewald formula. Findings . Patients with hypertension had higher lipid and lipoprotein levels than the controls and the values became more significant with increasing severity of hypertension. The difference was statistically significant for TC, LDL-C, and VLDL-C (P < 0.05 ). Conclusion . This study showed that lipid and lipoprotein cholesterol abnormalities exist and even worsen with severity of hypertension. It is important that investigations in patients with hypertension should include a lipid profile.